2019
DOI: 10.35808/ersj/1476
|View full text |Cite
|
Sign up to set email alerts
|

Customer Trust through Green Corporate Image, Green Marketing Staretgy and Social Responsibility: A Case Study

Abstract: Purpose:The aim of this study is to investigate the public awareness on the consumption of green products and their desire to reduce the impact of environmental damage, to propose green image, green marketing and corporate responsibility. Desigh/Methodology/Approach: The research was conducted through a survey method using customers of Unilever. The sample result was determined by the purposive sampling of 225 customers in Jakarta and its sorounding areas. Findings: The programs succeeded with the building of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In response to this, companies can provide green products for environmental sustainability as a form of responsibility for the environment (Widyastuti et al, 2019). Companies' responsibility to provide green products is one of the most important factors in promoting long-term growth and gaining a competitive edge (Saxena & Khandelwal, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to this, companies can provide green products for environmental sustainability as a form of responsibility for the environment (Widyastuti et al, 2019). Companies' responsibility to provide green products is one of the most important factors in promoting long-term growth and gaining a competitive edge (Saxena & Khandelwal, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The potential to increase consumer purchase intention and contribute to environmental sustainability and gain a competitive advantage to obtain a good image has piqued the interest of many researchers, including Honantha et al (2014), Johannes et al (2015), and Widyastuti et al (2019) who found a positive influence between green marketing and corporate image. Furthermore, Aji et al (2017), Agustina et al (2016), Aldoko et al (2016) found a positive influence between green marketing and purchase intention through the corporate image.…”
Section: Introductionmentioning
confidence: 99%
“…Setiawan et al (2020) tested the impact of service quality, price fairness, and customer satisfaction on customer trust in the airline industry using a structural equation model. Widyastuti et al (2019) tested the influence of green marketing and corporate social responsibility on customer trust using a structural equation model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Florence Nightingale stated, environmental health is considered a key issue raised in the development of green marketing strategies. The American Marketing Association (AMA) defines green marketing as the process of marketing for products that are assumed to be environmentally safe (Afifi and Amini 2018;Azmal et al 2014;Widyastuti et al 2019). This article is a literature review that discusses green marketing strategies to achieve sustainable competitive advantage.…”
Section: Introductionmentioning
confidence: 99%
“…of Hamid et al it was found that most customers who are less concerned about the environment are not interested in consuming green products.Without government appeals/regulations, the level of customer trust in green products is still underdeveloped, making them less concerned about the benefits produced(Widyastuti et al 2019). The lack of with green products tend to influence environmentally friendly purchasing decisions.…”
mentioning
confidence: 99%